Pengaruh Sosial Politik Terhadap Pembentukan Hukum Islam - Hasan, Hamsah; Marilang, Marilang; Kurniati, Kurniati (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2021)
This study focuses on the socio-political influence on the formation of Islamic law and vice versa. The establishment of Islamic law or tarikh al-Tasyri has begun since the early days of prophethood, the Khulafauurasyidin, Umawiya, Abbasid, Ottoman-era until entering the era of the Nation-State in the 15th century Hijriah. This research is a library research-based by tracing various references related to the discussion. This study found that the formation of Islamic law was marked by the birth of several products of Islamic law legislation that had existed from the late 80s until the early 90s. The birth of Islamic law products cannot be separated from the socio-political influences. The continuity of the existence of Islamic law and the state socio-politics influence and reinforce each other. In fact, this phenomenon is not only in Indonesia but also in many Muslim-majority countries.